1999
DOI: 10.4322/rbcv.2015.140
|View full text |Cite
|
Sign up to set email alerts
|

Doença pulmonar obstrutiva crônica em eqüinos da Polícia Militar do Estado do Rio de Janeiro

Abstract: Vinte e cinco eqüinos sem raça definida (S.R.D.), machos, com idades variando entre 6 e 24 anos, provenientes do sul do país, criados em regime de semiconfinamento, foram submetidos ao exame clínico e endoscópico do trato respiratório, à mensuração da pressão interpleural indireta (ventigrafia) e exame citológico de lavado broncoalveolar para a verificação da ocorrência da Doença Pulmonar Obstrutiva Crônica (DPOC). Além do exame clínico, foram avaliadas a freqüência respiratória, freqüência cardíaca e a temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…In a second study, 32 police horses were divided into healthy and asymptomatic mild/ moderate asthma groups based on their tracheal mucus scores, with the authors finding that the results were not influenced by the age of the animals. Finally, in another study, the group of police animals showed that 60% of the animals had signs of severe asthma, with more than 50% of neutrophils in the BAL fluid cytology in 36% of the horses investigated (Amaral et al, 1999).…”
Section: Bronchoalveolar Lavage (Bal) Fluidmentioning
confidence: 90%
See 1 more Smart Citation
“…In a second study, 32 police horses were divided into healthy and asymptomatic mild/ moderate asthma groups based on their tracheal mucus scores, with the authors finding that the results were not influenced by the age of the animals. Finally, in another study, the group of police animals showed that 60% of the animals had signs of severe asthma, with more than 50% of neutrophils in the BAL fluid cytology in 36% of the horses investigated (Amaral et al, 1999).…”
Section: Bronchoalveolar Lavage (Bal) Fluidmentioning
confidence: 90%
“…Asthma was present when at least two of the parameters were abnormal. They reported a occurrence of 60% of asthmatic horses, with all investigated animals presenting BAL fluid neutrophils above 10% (Amaral et al, 1999). In a similar population, also in Rio de Janeiro, the occurrence of mild to moderate asthma was found to be 43.4% of the horses evaluated, with all animals without clinical manifestations of asthma (Sad et al, 2012), while in riding horses, the occurrence of mild asthma was 17.4% and severe asthma was 4.3% (Lessa et al, 2005).…”
Section: Distributionmentioning
confidence: 97%
“…Em cavalos de policiamento na Cidade do Rio de Janeiro, foi detectada uma prevalência de 60% de DPOC, porém 100% dos animais examinados apresentaram algum estado inflamatório pulmonar, caracterizado por neutrofilia acima de 10% no lavado broncoalveolar (AMARAL et al, 1999). Nesta mesma população eqüina, aparentemente saudável, Lessa et al (2002) verificaram que 60% das amostras de lavado broncoalveolar apresentaram alterações compatíveis com quadros inflamatórios, sendo um compatível com DPOC e os demais (11) compatíveis com DIVA.…”
Section: Lista De Figurasunclassified